Respuesta :

Answer:

g=31/69

Step-by-step explanation:

-69g = -31

g = 31/69

Answer:

g = 6

Step-by-step explanation:

you need to combine like terms then isolate the variable. so, you can apply “add the opposite” and change the subtractions to additions and the number to its opposite notation.

-25g - (-8)g - (-7)g - (-29) = -31

-25g + 8g + 7g + 29 = -31

(combine like terms)

-10g + 29 = -31

(move the constant to the right by subtracting it from both sides of the equal sign)

-10g + (29 - 29) = -31 - 29

(isolate the variable by dividing by the coefficient)

-10g/-10 = -60/-10

g = 6

(check your answer by substituting 6 into the variables)